Habitat selection and potential antiherbivore effects of Peucetia flava (Oxyopidae) on Solanum thomasiifolium (Solanaceae) - Jacobucci, Giuliano B.; Medeiros, Lenice; Vasconcellos-Neto, Joao; Romero, Gustavo Q. [UNESP] (Amer Arachnological Soc, 2009)
Several spider species use plants as shelter and foraging sites, but the relationships among these organisms are still poorly known. Lynx spiders of the genus Peucetia do not build webs, and many species live strictly in plants bearing glandular trichomes. Peucetia flava Keyserling 1877 inhabits Solanum thomasifolium in southeastern Brazil and usually preys on herbivores and other small insects adhered to the glandular trichomes of its host plant. To evaluate the potential anti-herbivore protection. of this spider species for S. thomasifolium, we glued termites used as herbivore models oil trichomes of S. thomasifolium and on neighboring plants lacking glandular trichomes. leaf miner damage and spider density were recorded for S. thomasifolium plants in July 1997. There was a positive relationship between plant size and spider density. The removal or termites in S. thomasifolium by P. flava was higher than ill plants without glandular trichomes. The leaf miner damage was negatively related to spider density. Our results Suggest that P. flava may be all important plant bodyguard in the defense of S. thomasifolium from its natural herbivores.
Keywords: Animal-plant interactions; host plant specificity; lynx spider; plant protection